Physico-mechanical and thermal characteristics of commercially available and newly developed dental flowable composites - Kamalak, Hakan; Canbay, C. Aksu; Yigit, Oktay; Altin, Serdar (Elsevier Science Bv, 2018)
In this study, we investigated the structural stability, thermal conductivity, thermal analysis, materials' homogeneity of newly developed flowable composites. 6 different dental flowable composite resins; Grandio Flow (GF), Charisma Flow (CF), Tetric N Flow (TNF), Clearfil Majesty Flow (CMF),3M Filtek Ultimate Flow (3MFU), Voco Amaris Flow (VFA) were used. Restorations were made in standard teflon molds and the materials were light-cured for 20s in a 6 mm x 2 mm teflon mould. After polymerization, samples were kept in distilled water at 37 degrees C/24 h it was found that the composites have multiphase component such as metallic dopant and organic binder. The XRD investigation showed that there was a broad halo in the pattern which indicates the organic section in the composites. The FTIR results indicate the bond structure of the composites. The temperature dependence of the thermal conductivity of the composites were found below to 5 mW/K value depending on the type of the composites, which are low enough for dental application. The micro-hardness of the samples was analyzed and the result was compared. (C) 2017 Elsevier B.V. All rights reserved.
Keywords: FTIR; SEM-EDX; Micro-hardness; Porosity; Flowable composites